Does Timing of Ventricular Tachycardia Ablation Affect Prognosis in Patients With an Implantable Cardioverter Defibrillator? Results From the Multicenter Randomized PARTITA Trial. Issue 25 (3rd April 2022) - Della Bella, Paolo; Baratto, Francesca; Vergara, Pasquale; Bertocchi, Patrizia; Santamaria, Matteo; Notarstefano, Pasquale; Calò, Leonardo; Orsida, Daniela; Tomasi, Luca; Piacenti, Marcello; Sangiorgio, Stefano; Pentimalli, Francesco; et al.
Abstract : Background: Optimal timing for catheter ablation of ventricular tachycardia is an important unresolved issue. There are no randomized trials evaluating the benefit of ablation after the first implantable cardioverter defibrillator (ICD) shock. Methods: We conducted a 2-phase, prospective, multicenter, randomized clinical trial. Patients with ischemic or nonischemic dilated cardiomyopathy and primary or secondary prevention indication for ICD were enrolled in an initial observational phase until first appropriate shock (phase A). After reconsenting, patients were randomly assigned 1:1 in phase B to immediate ablation (within 2 months from shock delivery) or continuation of standard therapy. The primary end point was a composite of death from any cause or hospitalization for worsening heart failure. Amiodarone intake was not allowed except for documented atrial tachyarrhythmias. On July 23, 2021, phase B of the trial was interrupted as a result of the first interim analysis on the basis of the Bayesian adaptive design. Results: Of the 517 patients enrolled in phase A, 154 (30%) had ventricular tachycardia, 56 (11%) received an appropriate shock over a median follow-up of 2.4 years (interquartile range, 1.4–4.4), and 47 of 56 (84%) agreed to participate in phase B. After 24.2 (8.5–24.4) months, the primary end point occurred in 1 of 23 (4%) patients in the ablation group and 10 of 24 (42%) patients in the control group (hazard ratio, 0.11 [95% CI, 0.01–0.85]; P =0.034). The results met the prespecified termination criterion of >99% Bayesian posterior probability of superiority of treatment over standard therapy. No deaths were observed in the ablation group versus 8 deaths (33%) in the control group ( P =0.004); there was 1 worsening heart failure hospitalization in the ablation group (4%) versus 4 in the control group (17%; P =0.159). ICD shocks were less frequent in the ablation group (9%) than in the control group (42%; P =0.039). Conclusions: Ventricular tachycardia ablation after first appropriate shock was associated with a reduced risk of the combined death or worsening heart failure hospitalization end point, lower mortality, and fewer ICD shocks. These findings provide support for considering ventricular tachycardia ablation after the first ICD shock. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT01547208.